Study on Early Marriage Among the Current Generation in Negeri Latuhalat, Nusaniwe District, Ambon City - Lekatompessy, Elyana Imel; Lasaiba, Mohammad Amin; Manakane, Susan Evelin (Jurnal Pendidikan Geografi Unpatti, 2022)
Marriage is an agreement that binds men and women in a physical and spiritual bond. The purpose of this research is to examine marriage customs and their preservation. The study was conducted in Wainibe Village, Fenaleisela District, Buru Regency, with samples: ten traditional leaders and ten community leaders. In the modern era, the variables used are face-to-face marriages, meetings of the bride and groom, family agreements, and the completion of the marriage contract. The data analysis technique used in this research is descriptive analysis. The study results show that face swap marriage, or what is known as "ptukar face" in Buru, is a time-honored tradition that has existed since the ancestors. It applies to the 24 clans in a rush. Face swap marriage customs are marriages based on family agreements and traditional shops. Meeting of the bride and groom and traditional leaders and family in Christianity, marriage rules are sacred between one man and one woman who meet in love without being forced by anyone